ANALISIS PENGARUH FAKTOR KEPENDUDUKAN TERHADAP PERTUMBUHAN EKONOMI PROVINSI JAMBI - HM, Samsuddin (Jurnal Paradigma Ekonomika, 2013)
The results of theoretical studies showed population factors affect economic growth. Factors referred to are (1) the rate of population growth (2) labor force and (3) dependency ratio. The results of multiple regression model estimates show that of the three variables thought to affect economic growth, apparently only two variables, namely Population Growth (PG) and the Dependency Ratio (DR) are statistically significant effect at Î± 10 % and Î± 15 %. While variable labor force (LF) is statistically no effect on economic growth, but theoretically the labor force is one of the factors of production that also contribute to economic growth.Kata Kunci : Economic growth, Population growth, Labor Force and Dependency ratio